Curvature based DAD-method for damage localisation under consideration of measurement noise minimisation. (15th February 2019) - Erdenebat, Dolgion; Waldmann, Danièle; Teferle, Norman
Highlights: High-precise measurement of deflection line with photogrammetry. Consideration and smoothing of the measurement noise. Detection and localisation of structural stiffness changes and damages. Verification of the new DAD-method for damage detection on a laboratory experiment. Non-destructive load deflection experiment in the serviceability limit state. Abstract: Several research projects on condition assessment of bridges have proven that structural responses from dynamic excitation or static loading are influenced by local damages and thus, could be used for the detection and localisation of damages. Particularly, the curvature of structures is directly depending on their stiffness. In order to localise the discontinuities in curvature lines resulting from damage, this paper uses the so-called Deformation Area Difference Method (DAD), which is based on static load deflection tests on bridge structures. The DAD-method for damage localisation is presented within the paper using a theoretical example, which is then verified by two laboratory experiments. The first experiment consists of a reinforced concrete beam, which is loaded stepwise until failure of the concrete in the compression zone. Due to the load increase, the tensile zone of the beam starts cracking, leading to a stiffness reduction. The application of the DAD-method allows identifying the cracked area from the measurement of the deflection line. However, a challenge and a prerequisite for the applicability of the DAD-method is the highly accurate measurement of the deflection line. Therefore, one of the most modern measurement techniques such as digital photogrammetry is applied. Nonetheless, the accuracy of each measurement technique is limited. The second laboratory experiment consists of a steel beam, which is locally damaged at three positions. The degree of the damage is stepwise increased in order to identify at which degree of damage the applied DAD-method is still able to identify and localise damage. In this work, the focus lies on the minimisation of the effect of noise resulting from the limited measurement precision. Possible solutions were examined and proposed based on methods such as data smoothing using polynomial regression, consideration of standard deviation and measurement point variation. The reduction of the noise effect leads to an increase in the sensitivity of the damage localisation. The DAD-method has proven its potential for practical application through the successful localisation of cracking in the concrete beam.